A Near‐Infrared Organic Fluorescent Probe for Broad Applications for Blood Vessels Imaging by High‐Throughput Screening via 3D‐Blood Vessel Models (Small Methods 8/2021). Issue 8 (12th August 2021) - Abdul Sisak, Muhammad Asri; Louis, Fiona; Aoki, Ichio; Lee, Sun Hyeok; Chang, Young‐Tae; Matsusaki, Michiya
Abstract : Flexoelectric Effect In article number 2100338, Matsusaki and co‐workers report the discovery of an NIR blood vessel organic probe by screening a diversity‐oriented fluorescence library through an engineered three‐dimensional blood capillary‐based high‐throughput system. This physiologically reliable screening system showed stable and strong adsorption to the mouse endothelium post‐injection.